Ebola as a Case Study: The Role of Local Health Departments in Global Health Security. (March 2015) - Bevington, Frances; Kan, Lilly; Schemm, Katherine; Aldridge, Chris
Abstract : This article describes the role of local health departments in global health security and discusses Ebola outbreak as a case example.